Rh(iii)-catalyzed C–H activation/cyclization of benzamides and diazo compounds to form isocoumarins and α-pyrones1. Issue 12 (11th February 2015) - Li, Xing Guang; Sun, Min; Liu, Kai; Jin, Qiao; Liu, Pei Nian
<x xml:space="preserve">Abstract</x> Rhodium-catalyzed intermolecular cyclization of benzamides and diazo compounds via C–H activation has been achieved to construct C–C/C–O bonds for the first time.